PENERAPAN STANDARD OPERATING PROCEDUREPELAYANAN MAKANAN DI RESTORAN AQVA HOTEL LEGIAN-BALI - I Nengah Sandi Artha Putra; Widiantara, I Made Dedy; Wiantara, I Gusti Nyoman; Poetranto, Isa Wahjoedi Dwi (HARMONY HOSPITALITY, 2022)
Several things that become problems in service by waiters at the AQVA Hotel Restaurant, namely incompatibility with the Standard Operating Procedure of service in the Sequence of Service when taking orders. Therefore the purpose of this research is 1. To find out the application of the Standard Operating Procedure in food service at the AQVA Hotel Legian Restaurant, 2. To find out the obstacles faced in implementing the Standard Operating Procedure at the AQVA Hotel Legian Restaurant, 3. To find out the efforts made in overcoming the obstacles to implementing the Standard Operating Procedure at the AQVA Hotel Legian Restaurant. In this study, several instruments were used, such as: a list of questions that the author would use to interview the informants. This study uses qualitative descriptive data analysis techniques to process data obtained from the industry. The conclusion of the research is that the implementation of the Standard Operating Procedure in the Sequence of Service by waiters at the AQVA Hotel Restaurant has not been carried out properly and correctly, the type of menu used is Ala carte and uses American Service. Some of the obstacles experienced in hotels are not mastering SOPs, lack of manpower, not conducting briefings. Therefore the efforts made include: studying and understanding, adding manpower, and holding regular briefings.